Candidate traits for index selection in choice of oil palm ortets for clonal propagation - Soh, A.C.; Chow, C.S.; Iyama, S.; Yamada, Y. (Springer Science and Business Media LLC, 1994)
The objective of the study was to examine the usefulness of: principal component scores (PC), factor analysis cum stepwise regression identified traits (FASR) and selected traits based on their higher heritabilities and genetic correlations to the objective traits (HGC); as selection traits in a desired gains selection index (Yamada et al., 1975) to improve objective traits (oil yield, kernel oil yield, height increment, bunch index and leaf area ratio) as compared to those based on all the observed traits (AO); in selecting oil palm ortets for cloning. Based on the required selection intensities (i*) to achieve the desired gains AO indices having smaller i*'s were most efficient followed by PC, HGC and FASR indices. Expected selection response (1/i*), however, is expected to increase with additional selection traits. As such HGC (bunch number, kernel to fruit and mesocarp to fruit) and FASR (mesocarp to fruit, fresh fruit bunch yield, fruit to bunch and average bunch weight) indices would be useful as they achieved expected selection responses close to AO indices with a small number of traits and would also minimise the contribution of highly correlated traits to sampling errors. The results also suggested considering selection indices for only two objective traits-oid yield and kernel oil yield-instead of all five objective traits in which case screening of impracticably large populations is needed to obtain desired genetic gains.